1983
DOI: 10.1063/1.444679
|View full text |Cite
|
Sign up to set email alerts
|

An electron bombardment procedure for generating cation and neutral radicals in solid neon matrices at 4 K: ESR study of 14N2+ and 15N2+

Abstract: Articles you may be interested inSystematic theoretical studies of the interaction of 1,4-diazabicyclo [2.2.2]octane (DABCO) with rare gases ESR and a b i n i t i o theoretical studies of the cation radicals 1 4N+ 4 and 1 5N+ 4: The trapping of ion-neutral reaction products in neon matrices at 4 K A new generation technique for matrix isolated cations and neutrals involving the electron bombardment of the matrix sample during deposition is presented. Use of the method for the study of ion-neutral reactions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…The present value of b F for vЉ ϭ 0 is 1.6% (1.2) different from the matrix-isolation value (17), reaffirming the typical small effect of a rare-gas matrix on the hyperfine interaction. The difference in the value of the dipolar hyperfine constant t for vЉ ϭ 0 and vЉ ϭ 1 is 17% (4.7 standard deviations).…”
Section: Discussionsupporting
confidence: 79%
“…The present value of b F for vЉ ϭ 0 is 1.6% (1.2) different from the matrix-isolation value (17), reaffirming the typical small effect of a rare-gas matrix on the hyperfine interaction. The difference in the value of the dipolar hyperfine constant t for vЉ ϭ 0 and vЉ ϭ 1 is 17% (4.7 standard deviations).…”
Section: Discussionsupporting
confidence: 79%
“…ðX ; 0Þ ¼ À2420 ppm (ppm ¼ 10 À6 ), in agreement with an ESR value of )2400 ppm [14]. Further, cðX ; vÞ changes little up to v ¼ 5, and the same is expected for Dg ?…”
Section: Introductionsupporting
confidence: 77%
“…A survey of the experimental literature shows that the observed magnetic hyperfine coupling constants (hfccÕs) are internally consistent (i.e., the resulting spindensity is close to one) for X but not for B. Scholl et al [11] found A iso ðX ; 0Þ ¼ 102:4 MHz and A dip ðX ; 0Þ ¼ 23:3 MHz; both constants increase slightly between v ¼ 0 and v ¼ 2 [12,13]. (Here, MðN ; nÞ represents property M for the nth vibrational level of state N.) An electron spin resonance (ESR) study [14] on 14 N þ 2 (X) could only report isotropic values since free rotation of N þ 2 in the matrix made its full characterization impossible (A iso ðX ; 0Þ ¼ 104:1 MHz and hgi iso ¼ 2:0004). As shown in the literature [11][12][13][14], these hfccÕs give a total s-contribution of about 10%, in line with a singly occupied MO (SOMO) of type 2r g ðp r -p r Þ.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study of Nt ions in a neon matrix, a surface charge of 25 to 35 V was observed. 53 If we assume a surface potential of 10 V on a film 1000 A in thickness, then the surface-charge density must be about 10 11 charges (ions)/cm 2 • Molecular ions are easily dissociated by low-energy electron impact: For gas-phase Nt and at, the cross section for dissociation by low-energy-electron impact has been reported as about 2 x 10-16 cm 2 . 54 Combining these two numbers produces a predicted N+ yield of 2 x 10-5 ions per incident electron, compared with 8.5 x 10-7 ions per photon from Table 1.…”
Section: Photoelectron-stimulated Dissociation Of Surface Molecular Ionsmentioning
confidence: 99%